2020
DOI: 10.1016/j.jamda.2020.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Dilemmas With Restrictive Visiting Policies in Dutch Nursing Homes During the COVID-19 Pandemic: A Qualitative Analysis of an Open-Ended Questionnaire With Elderly Care Physicians

Abstract: Objectives: To mitigate the spread of COVID-19, a nationwide restriction for all visitors of residents of long-term care facilities including nursing homes (NHs) was established in the Netherlands. The aim of this study was an exploration of dilemmas experienced by elderly care physicians (ECPs) as a result of the COVID-19 driven restrictive visiting policy. Setting and Participants: ECPs working in Dutch NHs. Methods: A qualitative exploratory study was performed using an open-ended questionnaire. A thematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 16 publications
1
70
0
13
Order By: Relevance
“…Notably, residents in Green House homes receive significantly more hours per day of care from certified nursing assistants than do residents in traditional nursing homes. 14 Others have reported that visitor restrictions increase loneliness, depression, physical deterioration, and cognitive decline, 15 and so Green House/small NHs may convey an important psychosocial advantage. However, NHs <50 beds were not advantaged in the higher and extreme values compared with NHs ≥50 beds (their mortality rates at 75% and 90% percentile were markedly higher), which may speak to other critical differences.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, residents in Green House homes receive significantly more hours per day of care from certified nursing assistants than do residents in traditional nursing homes. 14 Others have reported that visitor restrictions increase loneliness, depression, physical deterioration, and cognitive decline, 15 and so Green House/small NHs may convey an important psychosocial advantage. However, NHs <50 beds were not advantaged in the higher and extreme values compared with NHs ≥50 beds (their mortality rates at 75% and 90% percentile were markedly higher), which may speak to other critical differences.…”
Section: Discussionmentioning
confidence: 99%
“…Insgesamt wurden 7224 Studienteilnehmende aus 14 Ländern berücksichtigt. Drei Studien schlossen Bewohner [ 3 , 12 , 28 ] und 4 Studien Angehörige ein [ 14 , 17 , 28 , 30 ], 10 Studien befragten Mitarbeitende [ 1 , 15 , 19 22 , 24 , 25 , 28 , 29 ]. Die Stichprobengröße reichte von 24 bis 1997 Teilnehmenden.…”
Section: Ergebnisseunclassified
“…In 6 Studien wurde von vermehrter Einsamkeit bei den Bewohnern durch die Besuchsrestriktionen berichtet [ 17 , 20 , 24 , 25 , 28 , 30 ]. Angst als Reaktion der Bewohner auf die Pandemie bzw.…”
Section: Ergebnisseunclassified
See 2 more Smart Citations